Thymidine Phosphorylase Expression and Microvascular Density Correlation Analysis in Canine Mammary Tumor: Possible Prognostic Factor in Breast Cancer - Zizzo, Nicola; Passantino, Giuseppe; D'alessio, Roberta Maria; Tinelli, Antonella; Lopresti, Giuseppe; Patruno, Rosa; Tricarico, Domenico; Maqoud, Fatima; Scala, Rosa; Zito, Francesco Alfredo; Ranieri, Girolamo (Frontiers in Veterinary Science, 2019)
Purpose: The thymidine phosphorylase (TP) is a key enzyme involved in the metabolism of pyrimidines. Inhibition or downregulation of this enzyme causes accumulation of me-tabolites with consequences in DNA replication. TP regulates angiogenesis and chemo-tactic activity of endothelial cells. Different studies showed the presence of TP upregula-tion in human cancer but the correlation between TP expression and the microvascular density (MVD) in canine mammary tumors is unknown. The aim of this study was to in-vestigate a possible correlation between the MVD and TP expression in tumor cells of canine mammary tumors of different degree of severity (G1-G3) by immunohistochemical analysis. Methods: 68 samples of spontaneous mammary neoplasia of 5-12 cm in diameter were collected from purebred and mixed-breed dogs (mean aged = 9.5+7), not subject to chemotherapy treatments in veterinary clinics. Histopathological analysis and immunostaining were performed. Results: Carcinoma simple samples have been classified as 72.06% of tubule-papillary, 20.59% cystic​-papillary and 7.35% tubular carcinomas. Immunostainings revealed a marked cytoplasmic expression of TP in 30.88% of samples, mild in 32.35%, weaker in 22.07% and negative in 14.70%. The correlation analysis and two-way ANOVA showed a linear correlation between MVD and TP with a coefficient of correlation (r)>0.5 (p <0.05) in G2 and G3. No correlation between variables was found in G1. Conclusions: These findings suggest that cytoplasmic TP overexpression is correlated with microvascular density in canine mammary tumors, in severe grade, and it can be a potential prognostic factor in breast cancer.